Psychological and pedagogical problems of improving the learning process - Dilbar Negmatovna Alimdjanova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Students of pedagogical universities lack pedagogical identification. One of the means to overcome this problem is pedagogical practice, where students can feel themselves in the role of teachers. The results of the internship show how important the connection with the school is for the professional growth of students.